Cultural Implications of the Kipsigis Clan Names (Impact: Journal of Transformation, 2026)
The present paper investigated the Kipsigis clan names under the major family name category with the aim of establishing the cultural implications in them. The study was done in Kericho and Bomet counties in Kenya from December 2023 to January 2025. Thirty clan names were collected and broken down into their components, and examined for their meaning, usage, and cultural context using a theory of personal names which was propounded by Makondo (2009) and principles from Lexical Pragmatics Theory by Wilson (2003) & Carston (2002). The findings of the analysis are that the Kipsigis society is structured into clans which were divided according to their origin into special clans, clans from the wider Kalenjin tribes, clans from the Maasai community and clans from Kisii community. Several cultural implications from the clan names were established. One is that that the Kipsigis value identity which they derive from clans. Second, they also value preservation of bloodlines by not allowing marriage between members of the same clan. Third, patriarchal system was seen in the tracing of lineage from fathers to sons beginning from the clans’ founding fathers. Fourth, their value for animals and connection to them is seen in the totems that every clan identifies with. Finally, through the clan system, preservation of the Kipsigis history is done in the oral narratives that each clan has of their lineage